(untitled) (Heritage, 2025)
LIBERATION OF PLAV, GUSINJE AND ROZAJE IN 1912. SUMMARY: Great powers decided that Turkey should renounce Plav and Gusinje with their surrounding to Montenegro. However, Turkey avoided to do this in many ways. To avoid all these complications at Montenegrinian – Turkish border great powers prepared a plan of compensating Plav and Gusinje for the territories on the East of Podgorica, including Albanian catholic tribes of Grude and Hote. Even though these territories for exchange were not valued neither for their area nor for quality of soil half the Plav-Gusinje area, Turkey continued to drag out to fulfill an obligation with the support of Austria – Hungary. In this situation great powers decided that the most suitable is to bring back to Montenegro, as a compensation for Plav and Gusinje, with the coast all the way to Bojana with a certain territory in the rear. The work of inter-state board for marking Montenegrinian – Turkish border was very slow so it will be done in summer in 1887. Besides marking Montenegrinian – Turkish border, turbulent state in their North-East part will last until the First Balkan War. Being afraid of bigger riots Turkey reinforced their garrisons in Plav, Gusinje, Rozaje and Berane in 1912. Montenegro couldn’t stay passive so it directly involved itself in the incidents. Montenegro sent an invitation to all Balkan states to start common actions against Turkish Empire. Montenegrinian government declared the war to Turkey on 8 October 1912. On the same day Eastern detachment , about 12600 soldiers and 32 cannons, under the command of Janko Vukotic, was directed toward Mojkovac, Bijelo Polje and Berane. As major part of Eastern detachment made progress toward Berane, Vasojevic brigade led pitched battles on the line of Mokra – Cakor – Plav – Gusinje. Being afraid that superior enemy could expel Gornje vasojevic brigade from its position, brigadier general Vukotic directed major part of Eastern detachment towards Plav and Gusinje right after the liberation of Berane on 16 October. Donje Vasojevic brigade got the mission to break through Gornje Bihore towards Rozaje. Gornje Vasojevic brigade entered Plav on 19 October, and a day after in Gusinje. Even though the progress of Donje Vasojevic brigade did not go as planned it managed to reject the enemy and liberate Rozaje and all the settlements on the left bank of the Ibar until 26 October.